Initial Assessment Of Facial Nerve Paralysis Based On Motion Analysis Using An Optical Flow Method - Sundaraj, Kenneth; W. Samsudin, Wan Syahirah; Ahmad, Amirozi; Salleh, Hasriah (IOS Press, 2016)
An initial assessment method that can classify as well as categorize the severity of paralysis into one of six levels according to the House-Brackmann (HB) system based on facial landmarks motion using an Optical Flow (OF) algorithm is proposed.The desired landmarks were obtained from the video recordings of 5 normal and 3 Bell’s Palsy subjects and tracked using the Kanade-Lucas-Tomasi (KLT) method.A new scoring system based on the motion analysis using area measurement is proposed.This scoring system uses the individual scores from the facial exercises and grades the paralysis based on the HB system.The proposed method has obtained promising results and may play a pivotal role towards improved rehabilitation programs for patients.